2017
DOI: 10.1177/1471301217726613
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the theoretical foundations of visual art programmes for people living with dementia

Abstract: Despite the growing international innovations for visual arts interventions in dementia care, limited attention has been paid to their theoretical basis. In response, this paper explores how and why visual art interventions in dementia care influence changes in outcomes. The theory building process consists of a realist review of primary research on visual art programmes. This aims to uncover what works, for whom, how, why and in what circumstances. We undertook a qualitative exploration of stakeholder perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 30 publications
(84 reference statements)
8
55
0
1
Order By: Relevance
“…There is no consensus on what arts interventions should include, and little has been done to identify their component parts (Burnside et al, 2017). Moreover, arts and dementia research lacks appropriate theoretical frameworks (Young, Camic and Tischler, 2016), and few studies have attempted to explain how the arts 'work' for people with dementia (Windle et al, 2017). Furthermore, the field has no common language to name and communicate the mechanisms and outcomes of arts interventions between multi-disciplinary partnersfor example artists, care staff, researchers, funders and people living with dementia (Gray et al, 2017).…”
Section: A Taxonomy Of Arts Interventions For People With Dementia: Amentioning
confidence: 99%
See 2 more Smart Citations
“…There is no consensus on what arts interventions should include, and little has been done to identify their component parts (Burnside et al, 2017). Moreover, arts and dementia research lacks appropriate theoretical frameworks (Young, Camic and Tischler, 2016), and few studies have attempted to explain how the arts 'work' for people with dementia (Windle et al, 2017). Furthermore, the field has no common language to name and communicate the mechanisms and outcomes of arts interventions between multi-disciplinary partnersfor example artists, care staff, researchers, funders and people living with dementia (Gray et al, 2017).…”
Section: A Taxonomy Of Arts Interventions For People With Dementia: Amentioning
confidence: 99%
“…The case study and the Delphi study re-confirmed that the Principles dimension could be interpreted as outcomes or mechanisms of arts interventions. The fluidity of the principles as outcomes or mechanisms is due to the complexity of arts interventions, and how these components interact with each other (Windle et al, 2014;Windle et al, 2017). For example, combined, or working in sequence, these elements can cause different or certain effects (Rogers, 2008).…”
Section: Explaining How the Arts 'Work'mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Billington, Carroll, Davis, Healey and Kinderman (2013) identified a number of features of effective facilitation, including addressing the participants by their names, maintaining good eye contact during engagement, speaking in a clear and loud but not commanding voice and creating a friendly atmosphere that allows people living with dementia to express themselves. A literature review by Windle, Gregory, Howson-Griffiths et al (2017) examined studies reporting visual arts programmes for people living with dementia, seeking "theoretical clues" (p.3) about the features that appear to contribute to the achievement of good outcomes and more positive and engaged experiences. They combined this with a qualitative exploration of stakeholder experiences of participation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role and value of the creative arts for people living with a dementia has been widely appreciated ( Young et al, 2016 ; Camic et al, 2017 ; Windle et al, 2017 ), yet it has not explicitly focused on the ability of people with a dementia to interact and engage as co-creators. This may also reflect different disciplinary aims and theoretical perspectives, and the location of the majority of theories of creativity within a cognitive framework ( Plucker and Beghetto, 2004 ) but may also be linked with dominant perceptions that people with a dementia are less capable of creative interactions ( Basting and Killick, 2003 ; Ullán et al, 2012 ).…”
Section: The Dementias and Creativitymentioning
confidence: 99%